189k views
9 votes
Y-5=3(x-1) in slope intercept form

User EoinS
by
5.4k points

1 Answer

11 votes

Explanation:


standard \: form \: \rightarrow \: slope - intercept \: form.

Slope-intercept form:


y = mx + b

Key:

m = slope.

m = slope.b = y-intercept.

How to solve?

Simplify the standard form equation algebraically.

Our equation:


y - 5 = 3(x - 1)

Use the Distributive Property:


y - 5 = 3x - 3

Add 5 to both sides of the equation:


y = 3x + 2

Therefore,


y = 3x + 2 \: is \: your \: slope - intercept \: form \: equation.

User Pavel Zagalsky
by
5.6k points